Dissertation Research & Writing for Construction Students - Naoum, S. G. (Shamil G.) (London : Routledge, 2013)
Aimed specifically at students on BSc and taught Masters programmes who are embarking on research for the first time, this book is clear with explanatory text supported by numerous examples illustrating good practice.
Previous ed.: London: Butterworth-Heineman, 2007.
Includes bibliographical references and index.
Keywords: Dissertations, Academic; Technical writing; Literature